The Right to Public Trial in Judicial Administrative Proceedings During the Covid-19 Pandemic - Sieniuć, Magdalena (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The aim of this article is to show the essence of the right to public trial in judicial administrative proceedings with a parallel analysis of the regulation contained in the Act of 2 March 2020 on special solutions connected with preventing, counteracting and combating COVID-19, other infectious diseases and crisis situations caused by them together with defining its relation to the provisions of the Law on proceedings before administrative courts, and consequently answering the question whether the mechanism for taking account of the indicated protected values inscribed in this relationship deserves approval, or whether in the era of the COVID-19 pandemic an attempt should be made to find another solution creating a sui generis “conflict rule” serving to ensure protection of these prima facie mutually exclusive values. The considerations carried out have shown that with regard to the protection of human health and life, which stand highest in the hierarchy of values protected by the legislator, it is legitimate to limit the right to an open hearing of a judicial-administrative case in favour of the form of a non-public sitting (closed session). However, the condition supporting the admissibility of such a mechanism for taking account of the values indicated is the holding of a non-public sitting in compliance with the rules of a fair trial, guaranteeing an impartial and fair hearing of the judicial-administrative case.